Retirement of professional soccer players - A systematic review from social sciences perspectives - Barth, M.; Güllich, A.; Forstinger, C. A.; Schlesinger, T.; Schröder, F.; Emrich, E. (Journal of Sports Sciences, 2021)
Retiring professional athletes face multifaceted changes and potential issues of adjustment, occupational development, and well-being, which raises concerns around the world. The study systematically reviewed the available research investigating professional soccer players` sport retirement from social sciences perspectives. The literature search in electronic databases and a "snowballing" procedure yielded 17 eligible studies investigating > 2,200 retired professional soccer players. The review followed the PRISMA statement. Nine studies focused on an early transition phase to retirement period; four studies investigated later periods of ten years or longer after retirement. Around half of the players reported involuntary retirement, often associated with declining performance and/or injury. Studies suggest issues of adjustment and mental health during early years after retirement, while psychological issues had apparently declined around 1-2 decades after retirement. However, available studies had notable limitations including lack of evidenced representative samples, report of measures` reliability, and control for confounders. Furthermore, while theoretical models emphasise a holistic perspective, quantitative research often took a narrow rather than holistic perspective. In summary, available knowledge is fraught with some uncertainty regarding reliability and representativeness of the population of retired professional soccer players. We offer future directions to advance the development of a theory of sport retirement.